2016
DOI: 10.1186/s12983-016-0173-x
|View full text |Cite
|
Sign up to set email alerts
|

The bear circadian clock doesn’t ‘sleep’ during winter dormancy

Abstract: BackgroundMost biological functions are synchronized to the environmental light:dark cycle via a circadian timekeeping system. Bears exhibit shallow torpor combined with metabolic suppression during winter dormancy. We sought to confirm that free-running circadian rhythms of body temperature (Tb) and activity were expressed in torpid grizzly (brown) bears and that they were functionally responsive to environmental light. We also measured activity and ambient light exposures in denning wild bears to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 66 publications
1
21
1
Order By: Relevance
“…Denning bears have sharply reduced levels of activity (Messier et al, 1994; Ware et al, 2012), but whether the circadian clock operates in denning polar bears is unknown. Mammals living in nonpolar regions that undergo deep hibernation or daily torpor exhibit a range of circadian characteristics including complete loss of circadian rhythmicity to apparent entrainment to environmental cues and expression of free-running rhythms (Körtner and Geiser, 2000; Heller and Ruby, 2004; Revel et al, 2007; Gür et al, 2009; Healy et al, 2012; Jansen et al, 2016). We identified denning events in the data set using a control chart-based algorithm applied to collar temperature data to identify extended periods of warm temperatures that are indicative of denning events because the insulated snow dens of polar bears result in the collar temperature sensor remaining well above ambient air (Olson, 2017; Rode et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Denning bears have sharply reduced levels of activity (Messier et al, 1994; Ware et al, 2012), but whether the circadian clock operates in denning polar bears is unknown. Mammals living in nonpolar regions that undergo deep hibernation or daily torpor exhibit a range of circadian characteristics including complete loss of circadian rhythmicity to apparent entrainment to environmental cues and expression of free-running rhythms (Körtner and Geiser, 2000; Heller and Ruby, 2004; Revel et al, 2007; Gür et al, 2009; Healy et al, 2012; Jansen et al, 2016). We identified denning events in the data set using a control chart-based algorithm applied to collar temperature data to identify extended periods of warm temperatures that are indicative of denning events because the insulated snow dens of polar bears result in the collar temperature sensor remaining well above ambient air (Olson, 2017; Rode et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Plotting of activity as actograms and period and phase analyses were carried out using custom MATLAB scripts (The MathWorks, Natick, MA), adapted from the code developed for Jansen et al (2016). The MATLAB scripts are publicly posted (https://osf.io/jqtge/).…”
Section: Characterization Of Activity Profilesmentioning
confidence: 99%
“…iii) It is also possible that serum factors affect bone metabolism indirectly through the modulation of circadian rhythm. Jansen et al, [23] showed when bear's fibroblasts were cultured with active and hibernation phase serum containing medium, cell molecular rhythm was akin to those of active and hibernation phases, respectively. Circadian rhythm can govern OC activity and formation through different pathways, such as: 1) Regulation of aryl hydrocarbon receptor nuclear translocator-like (Bmal1) in OC [54], 2) Modulation of Bmal1 in osteoblasts which leads to alteration in RANKL expression [55], and 3) β-adrenergic and glucocorticoid signaling in OC [56,57].…”
Section: Plos Onementioning
confidence: 99%
“…The use of bear serum for cell culture has been investigated in recent years. The in-vitro experiments have indicated that the use of active and hibernating bear serum for cell culture can induce active-like and hibernation-like cell responses, respectively [ 23 25 ]. For example, the use of hibernating bear serum inhibits proteolysis, and increases protein content in muscle cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…also influence the use of torpor (Adams 2010;Rintoul and Brigham 2014). The control of hibernation and daily torpor is one area of ongoing interest, particularly related to neural regulation and brain function (Schwartz et al 2013;Scherbarth et al 2015;Jansen et al 2016), bone loss due to inactivity (Doherty et al 2014;Ma et al 2015;Wojda et al 2016), fat storage and use (Frank and Storey 1995;Contreras et al 2014), maintaining cellular functions (Zhang et al 2014b;Yuan et al 2015), and the microbiome (Carey and Assadi-Porter 2017). Not all mammals adjust their torpor use the same way in response to environmental perturbation; Doty et al (2016) recently reported that daily torpor use after a wildfire decreased in lesser longeared bats (Nyctophilus geoffroyi), in contrast to increased torpor use reported for terrestrial small mammals.…”
Section: Homeostasismentioning
confidence: 99%